NATURE AND FUNCTION OF LANGUAGE - Tasya Nadira; Fitra Ilhamsyah (Jurnal Recoms, 2024)
The purpose of writing this article is to know the nature of language as a tool of social control. Previously we must first know the meaning of language it self. Language is a communication tool in the form of a sound symbol system produced by human utterances. Language consists of words or a collection of words, each of which has meaning, namely, the abstract relationship between words as symbols with objects or concepts represented by a collection of words or vocabulary by linguists arranged alphabetically, or in alphabetical order with, and an explanation of the meaning and then recorded into a dictionary. The language itself is utterance, so the nature of language is the utterance used by humans to express things both real and unreal, directly or indirectly, tangible and invisible, situations of past and present conditions. Language is used as a tool of social control, which means language functions as an influence on the attitudes and opinions of others. If this function applies properly, then all social activities will take place well too. With language one can develop personality and social values to a higher level of quality. language as a tool of social control functions to control communication so that people involved in communication can understand each other. As an example that illustrates the function of language as a tool of social control that is very easy for us to implement is as a means of reducing anger, another example of social control can be applied to self and society, such as textbooks, religious lectures, scientific speeches, discussions and service advertisements society.